2016
DOI: 10.3747/pdi.2016.00103
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Roseomonas gilardii Peritonitis in a Patient on Continuous Ambulatory Peritoneal Dialysis

Abstract: There have been only 5 reported cases of Roseomonas peritonitis in peritoneal dialysis (PD) patients (1-4). Our 61-year-old patient on continuous ambulatory PD (CAPD) presented with asymptomatic, cloudy peritoneal dialysate. Intraperitoneal (IP) cloxacillin and ceftazidime was initiated. Blood test results were as follows: C-reactive protein 168 mg/L, white cells 15.4 × 10 9 /L. Dialysate cell count was 40 cells/ mm 3 , predominantly polymorphs. Dialysate fluid cleared up on day 3, with corresponding negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was also found to be associated with immunocompromised patients (Marin et al, 2001). Other reports of bacteremia caused by the Roseomonas species were in vertebral osteomyelitis (Nahass et al, 1995), infected tooth (Diesendorf et al, 2017), endocarditis (Shao et al, 2019), and peritonitis (Malini et al, 2016). However, many reports in case studies suggests that the majority of the patients had underlying diseases, malignancy being the most common factor (Wang et al, 2012;Michon et al, 2014).…”
Section: Coccoidmentioning
confidence: 99%
“…It was also found to be associated with immunocompromised patients (Marin et al, 2001). Other reports of bacteremia caused by the Roseomonas species were in vertebral osteomyelitis (Nahass et al, 1995), infected tooth (Diesendorf et al, 2017), endocarditis (Shao et al, 2019), and peritonitis (Malini et al, 2016). However, many reports in case studies suggests that the majority of the patients had underlying diseases, malignancy being the most common factor (Wang et al, 2012;Michon et al, 2014).…”
Section: Coccoidmentioning
confidence: 99%
“…Overall mortality to Roseomonas species was reported by them to be at 1%. Because it is still a rare organism and due to paucity of clinical evidence, it is suggested that treatment duration be stretched to 3 weeks of antibiotics [ 8 ]. Hopefully, this will prevent the change in modality to hemodialysis which is always undesirable to patients.…”
Section: Discussionmentioning
confidence: 99%